A clinical illustration of short‐term mentalization‐based therapy for borderline personality disorder. Issue 8 (24th May 2022) - Juul, Sophie; Frandsen, Frederik W.; Bo Hansen, Sune; Sørensen, Per; Bateman, Anthony; Simonsen, Sebastian
Abstract: Objective: Mentalization‐based therapy (MBT) is an evidence‐supported, long‐term psychotherapy program developed to treat borderline personality disorder (BPD). A short‐term, 20‐week adaptation to the original MBT format including case formulation, psychoeducation, and group and individual therapy has recently been proposed. The current case material will illustrate how the recent adaptation to the mentalization‐based practice can enhance personality functioning using a short‐term format. Methods: Case material is presented to demonstrate the clinical application of short‐term MBT in the treatment of a young woman diagnosed with BPD who has a history of failed treatment attempts and who showed signs of affective dysregulation, unstable relationships, and intense abandonment anxiety. Results: The case illustration shows how short‐term MBT can facilitate improvement in personality functioning, specifically targeting situations in which the patient lost her temper and became overwhelmed by abandonment anxiety. By continuously employing therapeutic shifts toward greater autonomy and agency, and by maintaining a balanced empathetic therapeutic stance, the therapists were able to enhance the patients mentalizing and personality functioning. Conclusions: Short‐term MBT can be effectively implemented to enhance the mentalizing capacity and personality functioning in outpatients with BPD.